Analysis and optimisation of calcium content in menus and dairy offer in Croatian kindergartens - Ivana Rumora; Jasenka Gajdoš Kljusurić; Vesna Bosanac (Mljekarstvo)
The importance of healthy diet from the earliest age as well as its influence on human health is indisputable. Unbalanced diet in childhood can, along with unhealthy lifestyle (stress, smoking, physical inactivity), cause a number of diseases at a later age. Two week menus in 26 kindergartens from continental and coastal Croatia have been analysed, taking into consideration the type of kindergarten (public, private, or religious). The aim of this research is to determine the quality of the offer regarding the intake of milk and dairy products, which, regarding their bioavailability, represent a major source of calcium, an essential nutrient in the intensive growth phase of children and young people. Using basic statistics, significant differences were not determined neither in the regional offer of milk and dairy products in the different types of kindergartens nor in the content of calcium and phosphorus. Milk and dairy products were adequately represented in the weekly offer in both regions under observation, and the average offer contained 9.7±1.5 servings. Average content of calcium in daily menues is 714.5±235.9 mg, which is in agreement with dietary reference intake recommendations (300-800 mg) and Croatian recommendations (400-700 mg). Use of fuzzy logic in creating new daily menus, by combining the existing offers enabled significant enlargement of the set of nutritionally acceptable menus as well as a greater diversity of meals.